Prospective study of the additional benefit of plexus magnetic resonance imaging in the diagnosis of chronic inflammatory demyelinating polyneuropathy. (12th August 2019) - Jomier, F.; Bousson, V.; Viala, K.; Péréon, Y.; Magot, A.; Cauquil, C.; Bouhour, F.; Vial, C.; Bedat‐Millet, A.‐L.; Taithe, F.; Bresch, S.; Siri, A.; et al.
Abstract : Background and purpose: Hypertrophy/signal hyperintensity and/or gadolinium enhancement of plexus structures on magnetic resonance imaging (MRI) are observed in two‐thirds of cases of typical chronic inflammatory demyelinating polyneuropathy (CIDP). The objective of our study was to determine the additional benefit of plexus MRI in patients referred to tertiary centers with baseline clinical and electrophysiological characteristics suggestive of typical or atypical CIDP. Methods: A total of 28 consecutive patients with initial suspicion of CIDP were recruited in nine centers and followed for 2 years. Plexus MRI data from the initial assessment were reviewed centrally. Physicians blinded to the plexus MRI findings established the final diagnosis (CIDP or neuropathy of another cause). The proportion of patients with abnormal MRI was analyzed in each group. Results: Chronic inflammatory demyelinating polyneuropathy was confirmed in 14 patients (50%), as were sensorimotor CIDP ( n = 6), chronic immune sensory polyradiculoneuropathy ( n = 2), motor CIDP ( n = 1) and multifocal acquired demyelinating sensory and motor neuropathy ( n = 5). A total of 37 plexus MRIs were performed (17 brachial, 19 lumbosacral and 8 in both localizations). MRI was abnormal in 5/37 patients (14%), all of whom were subsequently diagnosed with CIDP [5/14(36%)], after an atypical baseline presentation. With plexus MRI results masked, non‐invasive procedures confirmed the diagnosis of CIDP in all but one patient [1/14 (7%)]. Knowledge of the abnormal MRI findings in the latter could have prevented nerve biopsy being performed. Conclusion: Systematic plexus MRI in patients with initially suspected CIDP provides little additional benefit in confirming the diagnosis of CIDP.